Dry and hot: the hydraulic consequences of a climate change–type drought for Amazonian trees. (19th November 2018) - Fontes, Clarissa G.; Dawson, Todd E.; Jardine, Kolby; McDowell, Nate; Gimenez, Bruno O.; Anderegg, Leander; Negrón-Juárez, Robinson; Higuchi, Niro; Fine, Paul V. A.; Araújo, Alessandro C.; Chambers, Jeffrey Q.
Abstract : How plants respond physiologically to leaf warming and low water availability may determine how they will perform under future climate change. In 2015–2016, an unprecedented drought occurred across Amazonia with record-breaking high temperatures and low soil moisture, offering a unique opportunity to evaluate the performances of Amazonian trees to a severe climatic event. We quantified the responses of leaf water potential, sap velocity, whole-tree hydraulic conductance ( K wt ), turgor loss and xylem embolism, during and after the 2015–2016 El Niño for five canopy-tree species. Leaf/xylem safety margins (SMs), sap velocity and K wt showed a sharp drop during warm periods. SMs were negatively correlated with vapour pressure deficit, but had no significant relationship with soil water storage. Based on our calculations of canopy stomatal and xylem resistances, the decrease in sap velocity and K wt was due to a combination of xylem cavitation and stomatal closure. Our results suggest that warm droughts greatly amplify the degree of trees' physiological stress and can lead to mortality. Given the extreme nature of the 2015–2016 El Niño and that temperatures are predicted to increase, this work can serve as a case study of the possible impact climate warming can have on tropical trees. This article is part of a discussion meeting issue 'The impact of the 2015/2016 El Niño on the terrestrial tropical carbon cycle: patterns, mechanisms and implications'.